The Generalized Quarternion p-Group of Order 2n : Discovering the Fuzzy Subgroups (2020)
In this paper, the classification of finite p-groups is extended to the cartesian product of the generalized quarternion group of order 2n with a cyclic group of order 2 which also belongs to the class of the famous nilpotent groups